Pengkinian Konstruksi Joglo Tanpa Empat Saka Guru: Studi Kasus: Pendopo Pura Agung Blambangan Banyuwangi - Christophorus Koesmartadi; Mohhamad Kusyanto (ATRIUM: Jurnal Arsitektur, 2022)
Title: Updating Joglo Construction Without Four Saka guru (Case Study of Pendopo Pura Agung Blambangan of Banyuwangi)   Current architectural developments to maintain its sustainability have reached the awareness stage to explore the potential for the diversity of archipelago architecture, one of which is exploring the potential for the Joglo traditional house for the future. The demand for wide spans often comes to the fore, so it is not uncommon for new construction designs to respond to the demands for wide spans free from pillars. However, a solution is needed to solve this problem. The pillars and their frames are the main part of the main reinforcement system for the roof load as a whole, so they become prerequisites on behalf of the Joglo. This writing aims to analyze the updated form of construction without pillars that still maintain the Joglo form. The research method uses a qualitative descriptive approach by examining the process of eliminating the four pillars of teachers by analyzing the reliability of the structural system of the Puri Agung Blambangan pavilion and the Sabha Swagata Blambangan pavilion in Banyuwangi, East Java. The research results show how the construction of the four pillars and their frames are believed to be the main strength to withstand the roof’s weight. The construction system without the four pillars of the guru and their frames reduces the rigidity of the building because the strength is transferred to the pillars on the edges of the building and does not reflect the joglo structural and construction system. Many knot points have appeared without the pillars and the framework of a construction system, increasing the risk of collapse.